The Wisdom of Youth: Essays Inspired by the Early Work of Jacques and Raïssa Maritain - Tanner, Norman (Asian Horizons, 2016)
Travis Dumsday, ed., The Wisdom of Youth: Essays Inspired by the Early Work of Jacques and Raïssa Maritain, Washington DC: American Maritain Association (distributed by The Catholic University of America Press), 2016, pp. xviii + 353. ISBN: 978-0-9827119-8-9 The large majority of the book’s twenty contributors — seven women and thirteen men — are from or now based in USA. Since this work on two French citizens is published by the American Maritain Association, the arrangement seems reasonable. It is explained, too, by the close links of Jacques Maritain (1882-1973) with neighbouring Canada. Together with his French compatriot Etienne Gilson, he played a crucial role in the early life of the Pontifical Institute of Medieval Studies (PIMS) in Toronto, holding the title of professor at the institute from 1933 to 1945: therefore within the period described in the book’s title as ‘the early work’ of the Maritains.